2016
DOI: 10.1002/jbm.a.35897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parameters on the quality of core‐shell fibrous scaffold for retinal differentiation of conjunctiva mesenchymal stem cells

Abstract: This article describes the coaxial electrospinning to generate core-shell fibers from polycaprolactone (PCL) and polyethylene glycol (PEG) for differentiation of conjunctiva mesenchymal stem cells (CJMSCs) into photoreceptor-like cells by delivery of taurine. Also, the effects of many parameters such as polymer concentration, nozzle collector distance, applied voltage, and outer solution flow rate on creation of the core-shell structure were examined. The morphology and structure of fibers were characterized u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In this study, a conductive scaffold consist of SF/rGo was fabricated by electrospinning method to evaluate electrical stimulus on the proliferation and differentiation of CJMSCs toward neural‐like cells. Electrospinning as an electrostatic technique includes the use of a high‐voltage electrostatic field to charge the polymer solution which results in the creation of solidified ultra‐thin fibers as a scaffold for biomedical and tissue engineering application . Nanofibrous scaffold gives an excellent opportunity to the tissue engineering field because of its similarity to native ECM .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a conductive scaffold consist of SF/rGo was fabricated by electrospinning method to evaluate electrical stimulus on the proliferation and differentiation of CJMSCs toward neural‐like cells. Electrospinning as an electrostatic technique includes the use of a high‐voltage electrostatic field to charge the polymer solution which results in the creation of solidified ultra‐thin fibers as a scaffold for biomedical and tissue engineering application . Nanofibrous scaffold gives an excellent opportunity to the tissue engineering field because of its similarity to native ECM .…”
Section: Discussionmentioning
confidence: 99%
“…Electrospinning as an electrostatic technique includes the use of a high-voltage electrostatic field to charge the polymer solution which results in the creation of solidified ultra-thin fibers as a scaffold for biomedical and tissue engineering application. 21,22,43 Nanofibrous scaffold gives an excellent opportunity to the tissue engineering field because of its similarity to native ECM. 44 To date, synthetic and natural biomaterials have been used for scaffold fabrication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous studies, our MTT assay results illustrated that viability of CJMSCs cultured on fibrin gel significantly enhanced relative to cells cultured on TCP surface. This might be due to the polymerization processes of the fibrin gel that can facilitate oxygen and nutrients diffusion for the transplanted cells [12,34,39,40]. In this study, we found that culture of CJMSCs in fibrin gel leads to promotion of CJMSCs differentiation into photoreceptor-like cells.…”
Section: Discussionmentioning
confidence: 63%
“…MTT absorbance was measured at 570 nm using a microplate reader (ELX800; BioTeK, Winooski, VT). C=C, and C-O, respectively (Elzein, Nasser-Eddine, Delaite, Bistac, & Dumas, 2004;Nadri, Nasehi, & Barati, 2017). For PPY spectra, the bandʼs absorption was located at 3,414, 1,546, 1,461, and 1,292 cm −1 , which are related to N-H, C=C, C-C, and C-C/C-N stretching vibrations, respectively (Su, Li, Yuan, & Yi, 2012).…”
Section: Cell Viability On Pcl/ppy/mwcnts Scaffoldmentioning
confidence: 99%